2020
DOI: 10.2147/jpr.s276449
|View full text |Cite
|
Sign up to set email alerts
|

<p>Severity of Wound-Related Pain and Associated Factors Among Patients Who Underwent Wound Management at Teaching and Referral Hospital, Northwest Ethiopia</p>

Abstract: Background: Wound management is one of the commonly performed procedures in hospitals. It can be a major source of pain and pain may be a frequently experienced but under-considered component of wound management. Therefore, we aimed to determine the severity of wound-related pain and identifying factors associated with it among patients who underwent wound management. Patients and Methods: An institutional-based, cross-sectional study was conducted from March to May, 2020 in the University of Gondar Comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…20 Anxiety, acute wound, baseline pain, and analgesia intake were significantly associated with the severity of WRP. 20 The severity of wound pain was different at different stages of the dressing changes. In our study, pain scores were highest during wound debridement (mean 6.45) and cleansing (mean 5.50).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…20 Anxiety, acute wound, baseline pain, and analgesia intake were significantly associated with the severity of WRP. 20 The severity of wound pain was different at different stages of the dressing changes. In our study, pain scores were highest during wound debridement (mean 6.45) and cleansing (mean 5.50).…”
Section: Discussionmentioning
confidence: 94%
“…A vast majority of participants (93.8%) reported WRP during procedures such as dressing changes and debridement. A study conducted in Northwest Ethiopia showed that the prevalence of moderate-to-severe WRP during wound management was 94.1% 20. Anxiety, acute wound, baseline pain, and analgesia intake were significantly associated with the severity of WRP 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[85,259] Opioids and acetaminophen are typically used to treat moderate to severe pain, while non-steroid anti-inflammatory drugs (NSAIDs) work best for inflammatory wounds. [260] Naproxen is an NSAID that competitively inhibits the cyclooxygenase isozymes resulting in analgesic and antiinflammatory effects. One study used the anti-inflammatory effect of Naproxen to accelerate wound healing in diabetic rats in the form of MNP.…”
Section: Pain Hemorrhage and Deeper Tissue Damagementioning
confidence: 99%
“…Частота хронізації болю під час Операції Об'єднаних Сил у пацієнтів після вогнепальних поранень складає більше 70% [1,6]. Відсутність якісного контролю над болем має вплив на віддалені результати лікування посттравматичних стресових розладів, що в свою чергу, впливає на якість життя [2,3]. Біль стає безпосередньою причиною зв'язку із обставинами, в яких пацієнт отримав поранення [4,5,7].…”
unclassified